Experiences of Postpartum Mood Disorders of Women With More Than One Child. (October 2013) - Robertson, Phyllis; Curtis, Russ; Lasher, Rebecca; Jacques, Sharon; Tom, Shelly J.
In this consensual qualitative research study, the postpartum mood disorder (PMD) experiences of 127 women who have more than one child were explored through an online survey. Implications for practice include an expansion in predictive factors and symptoms when screening for PMD and the identification of prevention and coping strategies useful in the education and treatment of women who experience PMD.